Prognostic Significance of the Ratio of Left Ventricular Myocardial Parameters According to Echocardiography and Electrocardiography Data (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
A comparison was made of the myocardial mass of the left ventricle of the heart (LVMM), calculated from echocardiography , unaveraged and averaged ECG data, and the effectiveness of these methods in identifying the dynamics of LVMM during antihypertensive therapy in patients was assessed.